Berlin Ewa Szwagrzyl. - Omilanowska, Małgorzata; Szwagrzyl, Ewa (Dorling Kindersley travel guides, 2000)
A guide to Berlin which covers all the major sights, museums, historic and modern buildings, parks and forests. Cutaways, floor plans and 3-D maps help the reader to explore sights including the Peramon Museum and Schloss Charlottenburg. Information is also given for hotels and restaurants.